Análise do perfil clínico-epidemiológico de pacientes internados por covid-no período de 2020 e 2021 em um hospital universitário. - SANTOS, Igor Moraes do Espírito (2023)
Subject: The COVID19 pandemic impacted the reality of the globe in the 20202021 biennium, representing a challenge for various spheres of human life. It was no different in the field of health, with scientific research being essential for a better understanding of the natural history of the disease. Objectives: To analyze the clinical and epidemiological profile of the hospitalized patients with COVID19 in a University Hospital, relating data from epidemiology, therapy and patients. Method: Data collection was made using physical records at the João de Barros Barreto University Hospital, in Belém (PA) and subsequent statistical analysis using Excel spreadsheets and applied statistical programs. Graphs were generated using the GraphPad Prism 9.3.1 program and the tests were performed using the GraphPad Prism 9.3.1 and BioEstat 5.4 programs. An alpha significance level of 5% was used. Results: 90 patients were studied, 62.2% referring to the period April/May 2020 and 37.7% to the same period in 2021. The average age of the patients was 57.9 ± 14.5 years (54 61 .8) in 2020 and 56.9 ± 13.0 years (52.3 – 61.4) in 2021. There was a higher frequency of males (p=0.0042), aged between 46 and 60 years (p<0.0001), coming from the Metropolitan Region of Belém (RMB). The most frequent signs and symptoms were dyspnea (94.6%), fever (92.2%) and cough (82%). In therapy, the highest frequency was the use of antibiotics (90.5%), followed by glucocorticoids (74.5%), prophylactic heparin (80.7%). The need for orotracheal intubation (66.3%) and admission to the intensive care unit (68.2%) were infrequent. The most common outcome was hospital discharge (70%) (p<0.0001). Diabetic patients (p<0.0319), those who required orotracheal intubation (p<0.0001) and those who required Intensive Care Unit (ICU) (p<0.0005) were the ones who most died. Conclusion: We identified with the present study that being a man, aged between 46 and 60 years and having Systemic Arterial Hypertension was the epidemiological combination for greatest risk to develop COVID19. Antibiotic therapy did not seem effective as a treatment for COVID19, and only its rational use is relevant in the individual clinical condition of each patient. Orotracheal intubation proved to be a procedure linked to poor prognosis, including the outcome of death.